The Thematic Construction of the Nuzul by ‘Abd al-Qādir Malāhisy in Bayān al-Ma’āni ‘alā Mushaf Tartīb al-Nuzūl - Wahidi, Ridhoul; Hamka, Muhammad (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
This research aims to examine the thematic construction used by ‘Abd al-Qādir Malāhisy in interpreting the Qur'an, particularly in his work Bayān al-Ma’āni. Using a qualitative method based on library research, this study analyzes how Malāhisy designs the main themes in his exegesis and how he connects verses that have semantic relations into a cohesive theme. The research results show that Malāhisy applies the principle of intertextuality in interpreting the verses of the Qur'an through contextual and linguistic approaches. He also combines semantic analysis and linguistic structure to explain the relationships between verses that have similar meanings in various surahs. This approach provides a more systematic understanding of the content of the Qur'an and enriches the treasury of thematic exegesis in Islamic studies, which can offer new insights into the understanding of Qur'anic verses more comprehensively. Penelitian ini bertujuan untuk mengkaji konstruksi tematik yang digunakan oleh ‘Abd al-Qādir Malāhisy dalam menafsirkan al-Qur’an, khususnya dalam karyanya Bayān al-Ma’āni. Menggunakan metode kualitatif berbasis studi kepustakaan, penelitian ini menganalisis bagaimana Malāhisy merancang tema-tema utama dalam tafsirnya dan bagaimana ia menghubungkan ayat-ayat yang memiliki hubungan semantik menjadi sebuah tema yang kohesif. Hasil penelitian menunjukkan bahwa Malāhisy menerapkan prinsip intertekstualitas dalam menafsirkan ayat-ayat al-Qur’an melalui pendekatan kontekstual dan linguistik. Ia juga menggabungkan analisis semantik dan struktur kebahasaan untuk menjelaskan hubungan antara ayat-ayat yang memiliki makna serupa dalam berbagai surah. Pendekatan ini memberikan pemahaman yang lebih sistematis terhadap kandungan al-Qur’an dan memperkaya khazanah tafsir tematik dalam kajian keislaman, yang dapat menawarkan wawasan baru dalam pemahaman ayat-ayat al-Qur’an secara lebih komprehensif.